Developmental Differences in the Relationships Between Sensorimotor and Executive Functions - Gordon-Murer, Chloe; Stöckel, Tino; Sera, Michael; Hughes, Charmayne M. L. (Frontiers in Human Neuroscience, 2021)
Background: There is evidence that sensorimotor and executive functions are inherently intertwined, but that the relationship between these functions differ depending on an individual’s stage in development (e.g. childhood, adolescence, adulthood). Objective: In this study, sensorimotor and executive function performance was examined in a group of children (n = 40; 8- 12 years), adolescents (n = 39; 13- 17 years), and young adults (n = 83; 18- 24 years) to investigate maturation of these functions, and how the relationships between these functions differ between groups. Results: Adults and adolescents outperformed children on all sensorimotor and executive functions. Adults and adolescents exhibited similar levels of executive functioning, but adults outperformed adolescents on two sensorimotor functioning measures (eye-hand coordination spatial precision and proprioceptive variability). Regression analysis demonstrated that executive functions contribute to children’s sensorimotor performance, but do not contribute to adolescent’s sensorimotor performance. Conclusion: These findings highlight the key role that developmental stage plays in the relationship between sensorimotor and executive functions. Specifically, executive functions appear to contribute to more successful sensorimotor function performance in childhood, but not during adolescence. It is likely that sensorimotor functions begin to develop independently from executive functions during adolescence, and therefore do not contribute to successful sensorimotor performance. The change in the relationship between sensorimotor and executive functions is important to take into consideration when developing sensorimotor and executive function interventions.